2016
DOI: 10.1111/nmo.12816
|View full text |Cite
|
Sign up to set email alerts
|

Changes of excitatory and inhibitory neurotransmitters in the colon of rats underwent to the wrap partial restraint stress

Abstract: The present results support the consistency of the WRS as a potential model where part of the human IBS signs and symptoms are reproduced. The changes in glial cells and in excitatory and inhibitory neurotransmitters might represent the substrate for the dysmotility and hypersensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…The WRS is considered a psychosocial stress model adequate to reproduce in the animals, some of the typical symptoms and signs of IBS . Accordingly, we recently reported functional and morphological alterations in WRS rat similar to those described in IBS patients and, presently, we demonstrate that repeated OB administration prevents most of the changes caused by the WRS, particularly those on the enteric nervous system. However, the cellular mechanism through which OB could interfere with the nerve structures is undefined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The WRS is considered a psychosocial stress model adequate to reproduce in the animals, some of the typical symptoms and signs of IBS . Accordingly, we recently reported functional and morphological alterations in WRS rat similar to those described in IBS patients and, presently, we demonstrate that repeated OB administration prevents most of the changes caused by the WRS, particularly those on the enteric nervous system. However, the cellular mechanism through which OB could interfere with the nerve structures is undefined.…”
Section: Discussionmentioning
confidence: 99%
“…A main role in the aetiopathogenesis of IBS has been attributed to a psychosocial stress and animal models based on this hypothesis and reproducing some of the most common IBS symptoms have been developed. We recently demonstrated in rats underwent to the wrap restrain stress (WRS) the development of an increased colonic activity and faecal excretion and, as in IBS patients, a mild inflammation in the mucosa . Interestingly, we also found important changes in glial cells and in excitatory and inhibitory neurotransmitters in the entire colonic wall, and an increase in CRF1r expressing myenteric neurons.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent experimental studies point to an equally important contribution of the gut CRFr1-2/CRF signaling to the GI stress response (20,47). In the GI tract the CRFr are expressed by enteric neurons (Fig.2) and mucosal cells (19,20,(48)(49)(50)(51)(52) and an upregulation of these receptors has been reported in the colon of male Wistar rats underwent to delayed stress-induced visceral hyperalgesia (37,44) and WRS (19,20).…”
Section: Cortocotropin Releasing Factor (Crf)mentioning
confidence: 99%
“…The efficacy of this test is confirmed by the development of an immediate hyperalgesia, quantifiable in colon-rectal distention (CRD) number (18), the inhibition of small intestinal transit, the stimulation of large intestinal activity and increased fecal excretion (17). We recently demonstrated that rats underwent to the WRS presented a low-grade mucosal inflammation with a significant increase in mast cells and eosinophylic granulocytes (19,20) that overlapped that described in colonic biopsies of IBS (21). Moreover, these animals showed important changes in the glial cells, in inhibitory and excitatory neurotransmitters and receptors that were interpreted as responsible for the dysmotility and hypersensitivity present in IBS patients.…”
Section: The Wrap Restrain Stress (Wrs)mentioning
confidence: 99%
See 1 more Smart Citation